Evaluación de sustratos orgánicos en la propagación del banano (musa x paradisiaca l.) clon williams en vivero - Ajila Gia, Laura Gabriela (Machala : Universidad Técnica de Machala, 2021)
The banana is a fruit originating in Asia and is cultivated in all tropical regions throughout the year. The main producing countries are India with 36.52% followed by China (13.53%), Indonesia (9.29%), Brazil (8.17%) and Ecuador (8.05%). In the latter it is of great importance in the social and commercial sphere, it is fundamental in the food diet of the population, for banana propagation from chives, immediate multiplication from corm, traditional propagation or strains, micropagation, propagation by organogenesis, the use of substrate in the nursery phase has great interest in the growth presenting physical, chemical and biological properties that allow a good germination and growth of the plant. The objectives of this research were: To determine the effect of organic substrates on the growth of banana corms (Musa x paradisiaca) clone Williams in nursery. This research was carried out at the Santa Inés Farm, belonging to the Academic Unit of Agricultural Sciences of the Technical University of Machala, located at km 5.5 of the Machala-Pasaje road. A completely randomized block design (DBCA) was applied, using polyethylene bags (0.20m X 0.30m) with three treatments and three replications, with a total of 180 experimental units with a separation between blocks of 0.80 m for each replication. The treatments were: T1 (79% loamy soil + 12% rice husk + 9% ground charcoal); T2 (54% loamy soil + 8% vegetable peat + 38% pumice); T3 (41% loamy soil + 28% pumice + 39% organic matter + 2% fine sawdust). The variables evaluated in this research were: sprouting percentage, plant height, pseudostem diameter, number of leaves, leaf length, leaf width, number of roots, root length, root weight, plant fresh weight and plant dry weight every seven days. The data obtained were analyzed with the IBM SPSS STATICS 25 software for the comparison of means using ANOVA of one factor (p≤0.05), where no significant differences were found in all the variables evaluated. Among the most representative results obtained from the research, it can be seen that when planted in T1 (79% loamy soil + 12% rice husk + 9% ground charcoal) and T2 (54% loamy soil + 8% vegetable peat + 38% pumice stone), they had the same sprouting percentage of 86.67%. In addition, in T2 the plants produced in this substrate were taller at 90 days with an average of 12.88 cm, pseudostem diameter at 90 days with 1.54 cm, number of leaves with 3.6 leaves, leaf length with 21.36 cm, leaf width with 10.32 cm, root length with 11.25 cm, root weight with 4.85 g, with T3, the number of roots presented an average of 2.7 roots greater than the two treatments. However, with T1, the plants presented higher fresh weight of the plant with 248.7 g and dry weight of the plant with 77.92 g, surpassing the substrate of treatment two. This research shows that the use of organic substrates with the best development was T2 (54% loamy soil + 8% vegetable peat + 38% pumice stone), because it provides good sprouting and allows us to obtain more vigorous seedlings in the nursery. It is recommended to continue evaluating with other existing substrates.
El banano es una fruta originaria de Asia cultivada en todas las regiones tropicales, durante todo el año. Los principales países productores son, India con 36,52% siguiendo por China (13,53%), Indonesia (9,29%), Brasil (8,17%) y Ecuador (8,05%). En este último es de gran importancia en el ámbito social y comercial, es fundamental en la dieta alimentaria de la población, para la propagación en banano desde cebollines, multiplicación inmediata desde cormo, propagación tradicional o cepas, micropagación, propagación por organogénesis, el uso de sustrato en la fase de vivero tiene gran interés en el crecimiento presentando propiedades físicas, químicas y biológicas que permiten una buena germinación y crecimiento de la planta. Los objetivos planteados en esta investigación fueron: Determinar el efecto de sustratos orgánicos sobre el crecimiento de cormos de banano (Musa x paradisiaca) clon Williams en vivero. La presente investigación se realizó en la Granja Santa Inés, perteneciente a la Unidad Académica de Ciencias Agropecuarias de la Universidad Técnica de Machala, ubicada en el km 5,5 de la vía Machala-Pasaje. Se aplicó un diseño de bloques completamente al azar (DBCA), utilizando bolsas de polietileno (0,20m X 0,30m) con tres tratamientos y tres repeticiones, con un total de 180 unidades experimentales con separación entre bloque fue de 0,80 m a cada repetición. Los tratamientos fueron: T1 (79% Suelo limoso + 12% cascarilla de arroz + 9% carbón molido); T2 (54% Suelo limoso + 8% turba vegetal + 38% piedra pómez); T3 (41% Suelo limoso + 28% piedra pómez + 39% materia orgánica + 2% aserrín fino). Las variables evaluadas en esta investigación fueron: porcentaje de brotación, altura de la planta, diámetro del pseudotallo, número de hojas, longitud de hojas, ancho de la hoja, número de raíces, longitud de raíz, peso de raíces, peso fresco de la planta y peso seco de la planta cada siete días. Los datos obtenidos se analizaron con el software IBM SPSS STATICS 25 para la comparación de medias se utilizó el ANOVA de un factor (p≤0,05), en donde no presenta diferencias significativas en todas las variables evaluadas. Entre los resultados más representativos obtenidos de la investigación se puedo apreciar que al sembrarse en el T1 (79% Suelo limoso + 12% cascarilla de arroz + 9% carbón molido) y T2 (54% Suelo limoso + 8% turba vegetal + 38% piedra pómez), tuvieron el mismo porcentaje de brotación de 86,67%. Además, en el T2 las plantas producidas en este sustrato fueron de mayor altura a los 90 días con un promedio de 12,88 cm, diámetro del pseudotallo a los 90 días con 1,54 cm, número de hojas con 3,6 hojas, longitud de hojas con 21,36 cm, ancho de hoja con 10,32 cm, longitud de raíz con 11,25 cm, peso de raíces con 4,85 g, con el T3, el número de raíces presentaron un promedio de 2,7 raíces mayor a los dos tratamientos. Sin embargo, con el T1, las plantas presentaron mayor peso fresco de la planta con 248,7 g y con peso seco de la planta con 77,92 g superando al sustrato del tratamiento dos. Con esta investigación se demuestra el uso de sustratos orgánicos de mejor desarrollo fue el T2 (54% Suelo limoso + 8% turba vegetal + 38% piedra pómez), debido que nos brinda una buena brotación y nos permite obtener plántulas de mayor vigor en vivero. Se recomienda seguir evaluando con otros sustratos existentes.
Keywords: BANANO; VIVERO; PROPAGACIÓN; CORMO